2006
DOI: 10.1103/physrevlett.97.177601
|View full text |Cite
|
Sign up to set email alerts
|

Local Phase Decomposition as a Cause of Polarization Fatigue in Ferroelectric Thin Films

Abstract: We show that lead zirconate titanate thin films undergo local phase decomposition during fatigue. The original remanent polarization of the fatigued film is completely restored after furnace annealing in an O2 atmosphere, following a significant regrowth of a perovskite phase from the pyrochlorelike structure. By comparing our data with other researchers' work on annealing of fatigued ferroelectric samples, we conclude that local phase separation is the generic reason for electrical fatigue in ferroelectrics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
104
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 28 publications
5
104
1
Order By: Relevance
“…The degraded sample (fatigued for 2×10 9 cycles) is found to be completely restored to the fresh state with an enhanced polarization through applying a high electric field (e.g., 1100 kV/cm) as indicated in inset of Figure 1a. This rejuvenated behavior in polarization thus excludes the effect of any permanent damages on the degradation, such as mirocracks 21,22 or nonferroelectric phase (e.g., pyrochlorelike phase in PZT 23 ), which leads to a reduced polarization being unable to be restored by electric stress. To further examine the characteristics of ferroelectric behavior in the fatigued samples, field-dependent coercive field ( c E ) and remnant polarization (P r ) for the fresh and fatigued samples are monitored and shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 96%
“…The degraded sample (fatigued for 2×10 9 cycles) is found to be completely restored to the fresh state with an enhanced polarization through applying a high electric field (e.g., 1100 kV/cm) as indicated in inset of Figure 1a. This rejuvenated behavior in polarization thus excludes the effect of any permanent damages on the degradation, such as mirocracks 21,22 or nonferroelectric phase (e.g., pyrochlorelike phase in PZT 23 ), which leads to a reduced polarization being unable to be restored by electric stress. To further examine the characteristics of ferroelectric behavior in the fatigued samples, field-dependent coercive field ( c E ) and remnant polarization (P r ) for the fresh and fatigued samples are monitored and shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 96%
“…This result is consistent with that observed in other material systems such PMN-PT, PZN-PT, and PIN-PMN-PT single crystals. 13,14,22,25 In summary, we found that h001i textured ceramics with 3% template content exhibits improved fatigue resistance due to the optimum balance between the defect density and domain mobility. As evident from the improved macroscopic P-E loop squareness and PFM results, the role of charged defects and domain size have the controlling influence on the fatigue behavior.…”
mentioning
confidence: 99%
“…Systematic loss of the switchable polarization under cyclic external field is known as polarization fatigue. [6][7][8] Several mechanisms have been proposed in literature for explaining the fatigue behavior of a ferroelectric material including accumulation of charged defects at domain walls leading to their pinning, 9 formation of space charge layer at ferroelectric-electrode interface, 10,11 formation of micro-cracks due to residual strain, 12,13 field-driven phase transition, 14 and field-driven diffusion of electrode metal to grain boundaries. 15 Depending upon the operating conditions (temperature, external field magnitude, and frequency) and microstructure of the material, one or more of these fatigue mechanisms can play the governing role.…”
mentioning
confidence: 99%
“…Then, a variety of preparation methods have been applied for the fabrication of PZT capacitors on various electrodes, and the problems, e.g., the polarization fatigue, imprint [2], retention [3,4] and low integration density [5] were analyzed and overcome to some extent. Recently, Lou et al proposed a fatigue mechanism that PZT thin films on Pt electrode undergo a local phase decomposition from perovskite to pyrochlore phase during the polarization fatigue [6]. Further efforts on the basic study are required for the PZT application to the reliable and high density FeRAM.…”
Section: Introductionmentioning
confidence: 99%